2004
DOI: 10.1074/jbc.m410372200
|View full text |Cite
|
Sign up to set email alerts
|

Acidocalcisomes and the Contractile Vacuole Complex Are Involved in Osmoregulation in Trypanosoma cruzi

Abstract: Trypanosoma cruzi, the etiologic agent of Chagas disease, resists extreme fluctuations in osmolarity during its life cycle. T. cruzi possesses a robust regulatory volume decrease mechanism that completely reverses cell swelling when submitted to hypo-osmotic stress. The efflux of amino acids and K ؉ release could account for only part for this volume reversal. In this work we demonstrate that swelling of acidocalcisomes mediated by an aquaporin and microtubule-and cyclic AMP-mediated fusion of acidocalcisomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
149
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 113 publications
(173 citation statements)
references
References 55 publications
9
149
0
5
Order By: Relevance
“…2B) or hyperosmotic ( Fig. 2C) conditions, we observed that staining of VP1 overlapped with that of GFP at the CVC region, in agreement with the previously reported fusion of these organelles under osmotic stress Rohloff et al, 2004). The lack of colocalization between GFP-TcRab32 and the acidocalcisome marker under isosmotic conditions could be attributed to the dynamic nature of the interaction between these two organelles.…”
Section: Colocalization Of Gfp-tcrab32 With Vp1 Under Osmotic Stresssupporting
confidence: 79%
“…2B) or hyperosmotic ( Fig. 2C) conditions, we observed that staining of VP1 overlapped with that of GFP at the CVC region, in agreement with the previously reported fusion of these organelles under osmotic stress Rohloff et al, 2004). The lack of colocalization between GFP-TcRab32 and the acidocalcisome marker under isosmotic conditions could be attributed to the dynamic nature of the interaction between these two organelles.…”
Section: Colocalization Of Gfp-tcrab32 With Vp1 Under Osmotic Stresssupporting
confidence: 79%
“…Hyperosmotic stress also resulted in a great increase in the size of the contractile vacuole. In previous work, we demonstrated that the TcAQP1 localized to the contractile vacuole was involved in the regulatory volume decrease after hyposmotic stress (36). Our present results suggest that TcAQP1 and the contractile vacuole are also involved in water efflux during hyperosmotic stress.…”
Section: Discussionsupporting
confidence: 58%
“…Fluorescence Microscopy-For co-localization with a glycosomal marker, T. cruzi Y strain epimastigotes slides were prepared as previously described (35). Antibody concentrations were as follows: affinity-purified rabbit anti-TcSPPS antibody at 1:4,000; supernatant from an anti-TbPPDK producing mouse hybridoma culture at 1:10; anti-mouse Alexa 488 at 1:1,000; anti-rabbit Alexa 546 at 1:1,000.…”
Section: Methodsmentioning
confidence: 99%